Struktur dan Nilai Pendidikan Karakter Novel "Si Jamin dan Si Johan" Karya Merari Siregar serta Pemanfaatannya sebagai Bahan Ajar Apresiasi Sastra SMP Kelas VII - Zuber, Zuber - (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2024)
This article will describe the structure and value of character education in the novel "Si Jamin dan Si Johan" by Merari Siregar and its use as a teaching material for literary appreciation for grade VII of junior high school. The research method used is descriptive with instrument techniques. The results of the study are intrinsically themed with misery, with protagonist and antagonist characters, with a forward plot, with a setting: Jakarta, time: afternoon, evening and night. The atmosphere created is sad and touching. The author uses a third person point of view, Betawi language style and various figures of speech. The message to be conveyed is, helping each other and a sense of caring. Character education values: religious, strong religious teachings are given since childhood, social for helping each other, honesty is the main key for someone, responsibility based on their roles and duties and hard work. As teaching materials, the elements of novel development, namely appreciating life, strengthening religion, strengthening brotherhood and honesty are relevant to be used as teaching materials in the seventh grade of junior high school.Keywords: character; education; structural.ABSTRAKArtikel ini akan mendeskripsikan  struktur dan nilai  pendidikan karakter  novel” Si Jamin dan Si Johan” karya Merari  Siregar serta pemanfaatannya sebagai bahan ajar apresiasi sastra kelas VII SMP. Metode penelitian digunakan  deskriptif dengan teknik instrumen. Hasil penelitian secara intrinsik bertema kesengsaraan, dengan tokoh protagonis dan antagonis, beralur maju, dengan latar tempat: Jakarta, waktu: siang, sore dan malam. Suasana yang dibangun sedih dan mengharukan. Pengarang menggunakan sudut pandang persona ketiga, gaya bahasa Betawi dan beragam majas. Amanat yang ingin disampaikan yakni, tolong menolong dan rasa kepedulian. Nilai pendidikan karakter: religius kuatnya ajaran agama diberikan sejak kecil, sosial untuk tolong menolong, kejujuran kunci utama bagi seseorang, tanggungjawab berdasarkan peran dan tugasnya serta kerjakeras.  Sebagai bahan ajar unsur pembangunan novel yakni menghargai hidup, menguatkan agama, merekatkan persaudaraan dan kejujuran relevan dijadikan bahan ajar di krlad tujun SMP.Kata Kunci: karakter; pendidikan; struktural